INTELLIGENCE ANALYSIS AND THE CIA – A HISTORICAL PERSPECTIVE: THE FOUR SUBSTANTIAL COMPONENTS OF THE DIRECTORATE OF INTELLIGENCE IN THE DAYS OF THE OFFICE OF NATIONAL ESTIMATES (1950 – 1973) - Dan ROMAN (Romanian Intelligence Studies Review)
The early 1950s brought significant changes in the internal organization of the CIA, as a result of problematic issues, limitations, and deficiencies that were noted in reports evaluating the Agency’s work. The most important changes have been in the CIA’s analytical area, which has seen a notable expansion, along with the diversification of intelligence activities. The dismantling of its first structure engaged in intelligence analysis, the Office of Reports and Estimates (ORE), was followed by a notable consolidation of these activities through new dedicated structures. Among these, the Office of National Estimates (ONE) in particular played a major role.